2011
DOI: 10.1038/onc.2011.111
|View full text |Cite
|
Sign up to set email alerts
|

Roles of BIM induction and survivin downregulation in lapatinib-induced apoptosis in breast cancer cells with HER2 amplification

Abstract: Lapatinib, a dual tyrosine kinase inhibitor of the epidermal growth factor receptor and human epidermal growth factor receptor 2 (HER2), is clinically active in patients with breast cancer positive for HER2 amplification. The mechanism of this anti-tumor action has remained unclear, however. We have now investigated the effects of lapatinib in HER2 amplification-positive breast cancer cells with or without an activating PIK3CA mutation. Lapatinib induced apoptosis in association with upregulation of the pro-ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 36 publications
3
64
0
1
Order By: Relevance
“…Furthermore, depletion of BIM by RNAi resulted in inhibition of crizotinib-induced apoptosis in gastric cancer cells with MET amplification, indicating that upregulation of BIM contributes to the induction of apoptosis by the MET-TKI in such cells. These findings are consistent with those of previous studies of lung cancer cells with EGFR mutations and breast cancer cells with HER2 amplification (13)(14)(15)(16)(17). However, our observations revealed that depletion of BIM did not completely abolish crizotinib-induced apoptosis, suggesting that another apoptotic regulator might contribute to MET-TKIinduced apoptotic cell death.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Furthermore, depletion of BIM by RNAi resulted in inhibition of crizotinib-induced apoptosis in gastric cancer cells with MET amplification, indicating that upregulation of BIM contributes to the induction of apoptosis by the MET-TKI in such cells. These findings are consistent with those of previous studies of lung cancer cells with EGFR mutations and breast cancer cells with HER2 amplification (13)(14)(15)(16)(17). However, our observations revealed that depletion of BIM did not completely abolish crizotinib-induced apoptosis, suggesting that another apoptotic regulator might contribute to MET-TKIinduced apoptotic cell death.…”
Section: Discussionsupporting
confidence: 82%
“…However, depletion of STAT3 by RNAi had no substantial effect on expression of XIAP and c-IAP1 in such cells (data not shown). Previous studies have shown that XIAP and c-IAP1 were not substantially affected by EGFR-TKIs in EGFR mutationpositive non-small cell lung cancer cells or by HER2-targeting agents in breast cancer cells positive for HER2 amplification (16,17). Given that inhibition of MET results in downregulation of XIAP and c-IAP1 in MET amplification-positive gastric cancer cells, the mechanism by which the expression of such proteins is regulated likely differs between MET and other receptor tyrosine kinases including EGFR and HER2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although their previous study suggested that the combination of NVP-BEZ235 and AZD6244 could be an alternative strategy for EGFR -mutant NSCLC cells ( 5 ), this combination failed to increase apoptosis in EGFR -mutant cells with low BIM expression in their current study. Another recent study demonstrated that NVP-BEZ235 combined with lapatinib increased apoptosis compared with each agent alone in PIK3CA -mutant breast cancer cells with high BIM expression ( 6 ). This combination should be assessed Insight into the molecular events underlying oncogenesis has prompted the development of new treatment approaches such as molecularly targeted therapies, which are overcoming the limited overall survival and severe side effects of traditional cytotoxic cancer therapeutics.…”
Section: In the Spotlightmentioning
confidence: 99%